The effect of a copolymer inhibitor on baryte precipitation - Ruiz-Agudo, C.; Putnis, Christine; Putnis, Andrew (Mineralogical Society, 2014)
In situ atomic force microscopy (AFM) experiments were used to study the effect of trace amounts of a commercial inhibitor on the (001) baryte surface during growth. The additive tested was a copolymer, used as a scale inhibitor in oil recovery (maleic acid/allyl sulfonic acid copolymer with phosphonate groups, partial sodium salt). The morphology of the growth was used to gain a better understanding of the inhibition mechanism. Without an inhibitor, barium sulfate growth occurred by 2D island nucleation and spreading. The addition of a small amount (0.1 ppm and 0.5 ppm) of copolymer inhibitor enhances 2D nucleation but blocks growth. Just 1 ppm of inhibitor blocks nucleation and growth by adsorption of a copolymer layer onto the baryte surface. Similarly in 3D studies, small amounts of inhibitor seem to act on growth and not on nucleation and larger amounts of copolymer act on both by adsorption of the copolymer to all baryte surfaces keeping the particles in their embryo stage.